(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The international country risk guide referred to the possibility of analyzing a country’s political risks using variables that included certain common or differentiated political characteristics that could become an identifiable characteristic of that country. The goal of analyzing such risks is to provide a method for quantifying and monitoring their consequences through multiple variables, including, but not limited to, the performance of financial markets. Such evaluation can be accomplished by assigning risk scores to a group of factors known as political risk elements, and despite the large size of the effects of these risks on market performance (sectors and companies), some parties avoid, ignore, or even include insufficient estimates that do not reflect their significance. As a result, the research problem focused on the idea that such levels of political risk might have a significant positive or negative impact on the performance indicators of the Iraq Stock Exchange. The ARDL model was used in the study to determine the direction and strength of the influence on the research sample. The study uncovered several results, the most important of which was that the voting process and accountability connected to the army’s intervention in politics, accountability, and democracy were among the most influential explanatory factors for the two models.